PRAKTIK JUAL BELI DI KAWASAN YANG DILARANG BERJUALAN OLEH PEMERINTAH DAERAH KABUPATEN SAMBAS DALAM PERSPEKTIF HUKUM ISLAM - Ibrahim, Ade (Lunggi Journal, 2024)
Buying and selling is the exchange of property on the basis of mutual willingness or transfer of property rights by obtaining other objects in exchange for the purpose of seeking profit (profit) based on the methods allowed in Islam. Buying and selling according to language is an absolute exchange. Work is one of the human activities to meet the needs of life. Islam also tells all people to work. In working, you should obey the applicable regulations in order to maintain security and order in the community. In fact, there are many traders who do not obey applicable regulations, such as Street Vendors (PKL) on Hasan Saleh street using sidewalks to sell, causing congestion and disturbing others around them. The Regional Government of Sambas Regency has regulated the issue of Street Vendors (PKL) in the Regional Regulation of Sambas Regency Number 7 of 2006 concerning "Public Order". The method used is an empirical sociological method, which examines phenomena that occur in the field related to community behavior. The object studied in this study is in the form of field objects that may be able to provide information related to this research. Based on the results of research that the practice of buying and selling carried out by street vendors (PKL) on the sidewalk starts in the morning at 08.00 until evening at 14.30. The means used to sell such as carts, pickets, tables and chairs, and hangers. Street Vendors (PKL) in areas that are prohibited from selling on Hasan Saleh Street, Sambas Regency are classified as legal and allowed buying and selling, however, when the buying and selling activities of Street Vendors (PKL) are not in accordance with the Regional Regulations of Sambas Regency, the form becomes buying and selling in the prohibited category.